Cost-effectiveness analysis of patent foramen ovale closure versus medical therapy alone after cryptogenic stroke. - Yoko Shijoh; Shota Saito; Zhehao Dai; Sachiko Ohde (PLoS ONE)
Background Closure of a patent foramen ovale reduces the risk of recurrent stroke compared with medical therapy alone in young patients with cryptogenic strokes revealed by randomized control trials. Some cost-effectiveness analyses outside Japan have shown that patent foramen ovale closure is cost-effective, but no studies have examined cost-effectiveness in Japan. The objective of this study is to assess cost-effectiveness, from the perspective of a Japanese healthcare payer, of patent foramen ovale closure versus medical therapy alone for patients with patent foramen ovale related to cryptogenic strokes. Methods A cost-effectiveness study was conducted by developing a decision tree and a Markov model. Probabilities and a 5.9-year time horizon followed the RESPECT study. Utilities and costs were based upon published studies and assumptions. All assumptions were assessed by experts, including a cardiologist and a statistical expert. The target population comprised patients with cryptogenic stroke and patent foramen ovale, aged 60 years or younger. The model was discounted at 2.0% and its cycle was one month. A willingness-to-pay threshold is set at $50,000 / quality-adjusted life years (QALYs). Incremental cost-effectiveness ratio was evaluated. Then one-way sensitivity analyses as deterministic sensitivity analysis, and probabilistic sensitivity analyses were performed to assess data robustness. Results Incremental quality-adjusted life years, incremental costs, and incremental cost-effectiveness ratio were 0.464, $13,562, and $29,208 per QALY gained, respectively. One-way sensitivity analysis showed that the stable state utility score difference between patent foramen ovale closure and medical therapy had the largest impact on incremental cost-effectiveness ratio. Patent foramen ovale closure is cost-effective at a stable state utility score difference of >0.051, compared with medical therapy. Probabilistic sensitivity analyses demonstrated that patent foramen ovale closure was 50.3% cost-effective. Conclusions Patent foramen ovale closure was cost-effective compared with medical therapy for Japanese patients with cryptogenic stroke who were ≤60 years.